A Generalized Solution of an Initial Boundary Value Problem Arising in the Mechanics of Discrete-Continuous Systems - E. P. Kubyshkin; O. A. Khrebtyugova (Моделирование и анализ информационных систем)
In this paper we define a generalized solution of an initial boundary value problem for a linear system of differential equations with one ordinary differential equation and two partial differential equations (a hybrid system of differential equations). We have proved the existence theorem for a generalized solution, its uniqueness, the correctness of the problem. An analytical formula for the solution is found. Such a system of differential equations arises in the study of discrete-continuum mechanical systems.